Four new saproxylic species of Paranura Axelson, 1902 (Collembola: Neanuridae: Neanurinae) from Japan - Kasai, Hiro; Sawahata, Takuo (Zootaxa, 2023)
Four new saproxylic species of the genus Paranura from Nagasaki, Nara, and Niigata provinces of Japan are described and illustrated in this paper. Paranura tsushimaensis sp. nov. is characterized by a dark blue body color, Abd. V four times as long as Abd. VI, 3+3 eyes, three ocular chaetae on the head, four ordinary chaetae De on Th. III, two ordinary chaetae Di on Abd. V, and all dorsal chaetae of Abd. VI in a unique reticulated plate. P. nakamurai sp. nov. is identified by its yellowish white body color, 2+2 eyes, tubercle Af on the head with two reticulated tubercles, and tubercles Di on Abd. V fused. P. alpicola sp. nov. is characterized by its yellow body color, 3+3 eyes, presence of complete chaetotaxy in the central area of the head, Th. II–III with two and three ordinary chaetae De respectively, and tubercles Di on Abd. V separate. P. convallis sp. nov. is identified by its orange body color, 3+3 eyes, head without chaeta O, three mandibular teeth, and Th. II–III with three and four ordinary chaetae De respectively. A key for all species of the genus Paranura is provided.